The Office of the Mufti contemporary Greece - Huseyin, Huse Mehmet (Kulliyyah of Islamic Revealed Knowledge and Human Sciences ,International Islamic University Malaysia, 1998)
The religious affairs of the Muslims in Greece are handled by the Office of the Mufti, which acts as a mediator between the Muslims and the government. This functions of this office which is recognized by the Greek government and in fact considered a government office are numerous. However, sisnce this office was established, there has not been any comprehensive study done in order to analyze the role played by this office. Therefore, there is a great need to conduct a study about this issue. This study is based on, the existing literature, and archives of the Mufti of Komotini in Greece. The methods used are historical, descriptive, and analytical. As for findings of this research, the office of Mufti is still relevant and significant fo the Muslim community in Greece. The Islamic law continues to be personal law of Muslims in this country. Office of Mufti deals mainly with the legal problems of the Muslims pertaining to the family and personal law. Musti deals with these issues both as a jurisconsult (Jufti, or fatwa-giver) and at times as a judge of the Islamic legal court. In addition he continues to fulfill his administrative duties as well. The analysis of the functions of Mufti shows us some degree of the adaptation of this institution to changing social conditions.